Hadith #4293 - Sunan al-Nasa'i - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ma'rwf bin Suwayd al-Jdhamy معروف بن سويد الجذامي أبو سلمة المصري; Yonus bin 'Abdul A'la al-Sadfi يونس بن عبد الأعلى بن ميسرة الصدفي (Sunan al-Nasa'i)
“The Messenger of Allah was upset one morning and Maimunah said to him: “O Messenger of Allah, you look upset today., He said: ‘Jibril, peace be upon him, had promised to meet me last night but he did not come, and by Allah, he never failed to keep an appointment,; The day passed, then he thought of a puppy that was beneath a table of ours. He ordered that it be taken out, and then he took some water In his hand and sprinkled it over the place where it had been. That evening, Jibril, peac
Grade:

Hadith #3483 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Ma'rwf bin Suwayd al-Jdhamy معروف بن سويد الجذامي أبو سلمة المصري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ)forbade the price paid for a dog.
Grade: Sahih